Risk factors for periprosthetic joint infection following primary total knee arthroplasty: a systematic review and meta-analysis - Li, Jiashun; Liu, Zhen; Wang, Zheng; Li, Deyu; Zhang, Heng; Hao, Shuo; Zhu, Qingxue; Yakufu, Maihemuti; Abulaiti, Ainikaer; Haibier, Abuduwupuer (Frontiers in Surgery, 2026)
ObjectivePeriprosthetic joint infection (PJI) represents a severe and devastating complication following primary total knee arthroplasty (TKA), leading to higher morbidity and implant failure. However, existing evidence regarding its risk factors remains inconsistent.MethodPubMed, Cochrane Library, Embase, China National Knowledge Infrastructure (CNKI), Wanfang Database, VIP Chinese Journal Database, and the Chinese Biomedical Literature Service System (SinoMed) were searched for primary studies from the database inception to August 2025. Data were managed with EndNote X9 software, meta-analyses were performed using Review Manager 5.4, infection risk was analyzed using STATA 18, and the comprehensive incidence rate of PJI was analyzed using R 4.5.1.ResultsA total of 1,569 studies were identified, of which 20 were included in this systematic review. The meta-analysis including 20 studies analyzed eight risk factors: longer operation time (OR = 9.10, 95% CI: 7.66–10.80), obesity (OR = 13.95, 95% CI: 12.06–16.14), male gender (OR = 2.67, 95% CI: 1.80–3.95), diabetes (OR = 2.98, 95% CI: 2.27–3.92), longer hospital stay (OR = 1.73, 95% CI: 1.38–2.16), use of immunosuppressants (OR = 5.76, 95% CI: 2.77–11.98), hypoalbuminemia (OR = 6.24, 95% CI: 4.00–9.73), and underlying systemic inflammatory disease (OR = 3.47, 95% CI: 1.92–6.27). All identified risk factors were associated with an increased risk of developing PJI after primary TKA.ConclusionThe meta-analysis confirmed that longer operative time, obesity, male gender, diabetes, longer hospital stay, use of immunosuppressants, hypoalbuminemia, and underlying systemic inflammatory disease are risk factors for PJI after primary TKA. This systematic review and meta-analysis provide Level II evidence (according to the Oxford Centre for Evidence-Based Medicine criteria) for the identified risk factors.